Comparison of pain assessment by critical care pain observation tool and physiological variables in mechanically ventilated patients - Arjyal, Batsalya; Kumar Rajbanshi, Lalit; Khanal, Kanak; Man Singh, Dipesh; Regmi, Gunjan; Sangroula, Rakshya (Journal of Nepalese Society of Critical Care Medicine, 2023)
Background and aims: Critically ill and mechanically ventilated patient cane experience mild to severe pain. Pain assessment in critically ill mechanically ventilated patient is challenging due to their inability to communicate. In these patients, pain is often underdiagnosed and undertreated contributing to increased morbidity and mortality. The Critical-Care Pain Observation Tool (CPOT) is a tool designed to assess pain in critically ill patient. This study compares the accuracy of CPOT and physiological variables of pain for assessing pain in mechanically ventilated, critically ill patients in Intensive Care Unit (ICU). Methods: This quantitative observational study was conducted on critically ill mechanically ventilated patient. CPOT and physiological variables for assessment of pain were compared. The data of 120 samples were collected from 40 patients at three different time points (morning, evening and night) within 24 hours of ICU admission. Tracheal suctioning and patient positioning were considered as the two painful conditions in this study. Data were collected for CPOT and physiological variables (heart rate and blood pressure) at rest and at the time of these two painful procedures. Results: There was a significant increment in physiological variables during the painful procedures. The CPOT score values also increased, coinciding with increase in physiological variables. There was statistically significant correlation between the increase in CPOT score and physiological variables. Conclusion: The study demonstrates a significant correlation between the change in CPOT score and physiological variables in response to painful stimuli in mechanically ventilated critically ill patients.